Useful woody species from tropical deciduous forest in Sierra de Nanchititla, Mexico - Zepeda Gómez, Carmen; Aguilar, Cristina Burrola; Olascoaga, Laura White; Soto, Clarita Rodríguez (Instituto de Ecología, A.C., 2017)
The tropical deciduous forests are highly diverse communities whose distribution and conservation status are compromised by human activities. The purpose of this research was to document the traditional use given to the woody and arborescent flora of the deciduous forests in Sierra de Nanchititla and to identify potential species for the recovery, permanence or sustainable use of the regional deciduous forests. The work was performed by ethnobotanical scans with the application of open interviews with key informants included in the Sierra Nanchititla Nature Reserve. One hundred thirty-seven useful woody species were recorded; nine botanical families grouped 58% of the flora; Fabaceae was the family with the largest number of genera and species. From the recorded species, 85% are considered native to Mexico; the endemic component exhibited the greatest number of species (30%), followed by Mesoamerican species (26%) and Neotropical (21%). Nine plant uses were recorded; the most frequent was medicinal followed by building and fuelwood uses. Of the flora, 32.8% (45 species) was useful for three or more purposes, Enterolobium cyclocarpum showed the greatest uses number (six). Thirty-four species were cited for food use primarily by their fruits production. Sixteen species have high ecological restoration and reforestation potential because they are multipurpose Mexican species and important providers of environmental services; its use in restoration programs could meet some local demands, maintain tree cover and local diversity.